Surgical treatment of congenital malenocytic nevus of cheek in adult: an interesting case report - Gupta, Madhusoodan; Varshney, Deepti (International Journal of Research in Medical Sciences, 2021)
Congenital melanocytic nevus (CMN) is a rare disease, which is present from birth. CMN has pigmented surface and hairs. CMN are classified in three types according to their size, small size less than 2 cm, medium size 2-20 cm and large or giant size more than 20 cm. If CMN is present over the cheek it causes significant aesthetic deformity. It poses a great challenge to aesthetic and reconstruction surgeon to excise and reconstruct this lesion over the cheek. Cheek is central facial unit and make the largest part of face. Here author presents a case of 20 years old young female who had medium size congenital melanocytic nevi over the left cheek at malar aesthetic subunit. Author planned a single stage excision followed by primary closure. Wound healed well without any complication and sutureline was camouflaged in left nasolabial crease with good aesthetic result.